High-flow nasal oxygen in acute hypoxemic respiratory failure: A narrative review of the evidence before and after the COVID-19 pandemic - Genecand, Léon; Agoritsas, Thomas; Ehrensperger, Charlotte; Kharat, Aileen; Marti, Christophe (Frontiers in Medicine, 2022)
High Flow nasal oxygen (HFNO) is a non-invasive advanced respiratory support that allows the delivery of high flow and humidified air through large bore nasal cannula. It can deliver a higher inspired oxygen fraction than conventional oxygen therapy (COT), improves secretion clearance, has a small positive end-expiratory pressure, and a washout effect of the upper air space that diminishes dead space ventilation. HFNO has been shown to reduce the work of breathing in acute hypoxemic respiratory failure (AHRF) and became an interesting option for non-invasive respiratory support. Evidence published prior to the COVID-19 pandemic, suggested a possible reduction of the need of invasive mechanical ventilation compared to COT. The COVID-19 pandemic has resulted in a substantial increase of AHRF worldwide, overwhelming both acute and intensive care units capacity in most countries. This triggered new trials adding to the body of evidence on HFNO in AHRF and its possible benefits compared to COT or non-invasive ventilation. We summarize and discuss this recent evidence to inform the best supportive strategy in AHRF both related and unrelated to COVID-19.